1991
DOI: 10.1128/jcm.29.4.696-701.1991
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a strain-specific Entamoeba histolytica cDNA clone

Abstract: Entamoeba histolytica is an intestinal parasite causing significant morbidity and mortality worldwide. More tools are needed to understand the epidemiology and molecular pathogenesis of amebiasis. A cDNA library was constructed by using poly(A)+ RNA isolated from an axenic strain of E. histolytica, HM1:IMSS, which expresses a pathogenic isoenzyme pattern (zymodeme). Differential screening of the library yielded a strain-specific 3' polyadenylated cDNA clone, C2, possessing nine 26-nucleotide tandem repeats. RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Recently, the polymorphic structure of E. histolytica has been described. [32][33][34][35] Polymorphic DNA loci have been characterized both in proteincoding 36,37 and noncoding 33,35,38 sequences. These polymorphic loci are potentially useful in the molecular epidemiology of amebiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the polymorphic structure of E. histolytica has been described. [32][33][34][35] Polymorphic DNA loci have been characterized both in proteincoding 36,37 and noncoding 33,35,38 sequences. These polymorphic loci are potentially useful in the molecular epidemiology of amebiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Single-copy genomic DNA sequences encoding a 125-kDa surface antigen that differed between pathogenic and nonpathogenic isolates but were 90% similar in nucleic acid sequences made up the basis for differentiation of isolates by DNA probes and restriction enzyme fragment length polymorphism analysis of PCR products (33,121). A DNA clone isolated from a cDNA library containing 26-nucleotide tandem repeats was found to distinguish between xenically cultured pathogenic and nonpathogenic E. histolytica strains; however, this sequence was not present in all axenically cultured pathogenic strains (17). Two pairs of oligonucleotide primers targeted to sequences coding for a 30-kDa surface antigen were the basis of a PCR assay discriminating between pathogenic and nonpathogenic laboratory isolates (120), while another 30-kDa assay featured multiple sets of primers and restriction enzyme analysis to differentiate pathogenic from nonpathogenic laboratory isolates (119).…”
Section: E Histolytica-pathogenic Versus Nonpathogenic Isolatesmentioning
confidence: 99%
“…Entamoeba infection can be divided into symptomatic and asymptomatic. Asymptomatic individuals tend to be infected/colonized by mostly non-pathogenic and commensal Entamoeba species, primarily Entamoeba dispar (E. dispar), rather than the pathogenic E. histolytica [15][16][17]. In fact, Herbinger et al (2011) demonstrated that, in a cohort of 5378 travelers returning back to Germany from elsewhere with symptoms of intestinal infections, PCR had detected E. histolytica and E. dispar in 9.7% and 88.3% of cases, respectively; more importantly, however, was the fact that almost all of those with PCR evidence of E. histolytica had symptoms typical of amebiasis, compared with only half with evidence of E. dispar [18].…”
Section: Epidemiologymentioning
confidence: 99%
“…The rest of those with E. dispar were determined to be coinfected with other organisms such as Campylobacter spp., Giardia lamblia, and Salmonella typhi. Moreover, some studies have even showed E. dispar colonization in completely asymptomatic HIV-positive individuals, with no evidence of mucosal invasion [15,19].…”
Section: Epidemiologymentioning
confidence: 99%